Responses of Grower-Finisher Pigs to Diets Containing Varying Levels of Wheat Bran with or without Optizyme - An Exogenous Enzyme Complex (Journal of Science and Technology, 2016)
Three isonitrogenous diets containing 20, 30 and 40% wheat bran (WB) were formulated and fed ad libitum to grower-finisher pigs. The 20% WB diet was the Control diet while the 30% and 40% WB diet were described as the experimental diets and both of these had 50g. of an exogenous feed enzyme complex known as OPTIZYME added to every 100kg of the diet. A total of 15 pigs in 5 replicates were used for the study which was terminated when the individual pigs attained liveweight of 70 ± 0.5kg.The mean values for daily weight gains and feed conversion efficiency were similarly (p>0.05) for the pigs fed the 3 diets but mean daily feed intake was highest (P